2018
DOI: 10.1007/s13205-018-1392-y
|View full text |Cite
|
Sign up to set email alerts
|

Addition of ionophore A23187 increases the efficiency of Cocos nucifera somatic embryogenesis

Abstract: The present study reports the effect of treatment of coconut embryogenic structure explants (derived from embryogenic callus) with the calcium ionophore A23187 (0, 1, 5, 10 µM) to promote somatic embryogenesis under in vitro conditions. The results showed no significant increase in the percentage of explants forming embryogenic callus, but with 1 µM ionophore there were significant increases in the formation of embryogenic structures per callus (2.8-fold), of somatic embryos per callus (1.5-fold) and also a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…It was reported to produce 2.8-fold embryogenic structures per callus, 1.5-fold somatic embryos per callus and 1.5-fold developing plantlets per callus. Further, it was observed that the greater expression of CnCERK (Coconut Somatic Embryogenesis Receptor Kinase) gene at initial stages of the culture period under the ionophore treatment (Rivera-Solis et al, 2018). In the present study, significant amount of embryogenic structures were obtained with calcium ionophore treatments when 2,4-D was used as the growth regulator.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…It was reported to produce 2.8-fold embryogenic structures per callus, 1.5-fold somatic embryos per callus and 1.5-fold developing plantlets per callus. Further, it was observed that the greater expression of CnCERK (Coconut Somatic Embryogenesis Receptor Kinase) gene at initial stages of the culture period under the ionophore treatment (Rivera-Solis et al, 2018). In the present study, significant amount of embryogenic structures were obtained with calcium ionophore treatments when 2,4-D was used as the growth regulator.…”
Section: Discussionmentioning
confidence: 46%
“…Medium III contained 1 µM 2,4-D and 1 µM 22(S),23(S)-homobrassinolide. For T1, T3, T5 and T7 cultured translucent structures were treated with 10 µL of 1µM calcium ionophore A23187 deposited with a micropipette on the explant (Rivera-Solis et al, 2018).…”
Section: M E D I a P Re P A R A T I O N A N D C U L T U Re Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gibberellic acid increased the expression of CnKNOX1 and decreased the expression of CnKNOX2 [74]. Treatment of coconut somatic embryogenic calli with A23187 ionophore promoted the rate of SE by increasing the somatic embryo formation and plantlets, and by altering the expression of the SERK gene [101]. Modulating the expression of these genes using exogenous chemicals may be very useful to enhance the development of coconut SE.…”
Section: Molecular Control Of Somatic Embryogenesis In Coconutmentioning
confidence: 99%